On the morphological behavior of ABC miktoarm stars containing poly(cis 1, 4‐isoprene), poly(styrene), and poly(2‐vinylpyridine). Issue 22 (3rd October 2018) - Chernyy, Sergey; Mahalik, Jyoti P.; Kumar, Rajeev; Kirkensgaard, Jacob Judas Kain; Arras, Matthias M. L.; Kim, Hyeyoung; Schulte, Lars; Ndoni, Sokol; Smith, Gregory S.; Mortensen, Kell; Sumpter, Bobby G.; Russell, Thomas P.; et al.
ABSTRACT: Fundamental understanding of microphase separation in ABC miktoarm copolymers is vital to access a plethora of nonconventional morphologies. Miktoarm stars based on poly( cis 1, 4‐isoprene) (I), poly(styrene) (S), and poly(2‐vinylpyridine) (V) are model systems, which allow systematic studies of the effects of composition, chemical microstructure, and temperature on the thermodynamics of microphase separation. Eleven ISV‐ x (I:S:V = 1:1: x, v : v : v ) miktoarm copolymers were synthesized by anionic polymerization affording well‐defined copolymers with a variable V arm. Equilibrium bulk morphologies of all samples, as evidenced by small‐angle X‐ray scattering, transmission electron microscopy (TEM), and self‐consistent field theory, showed a systematic transition from lamellae ( x ≈ 0–0.2) to [8.8.4] tiling ( x ≈ 0.6–0.9) to cylinders in undulating lamellae ( x ≈ 2–4) and, finally, to hexagonally packed core–shell cylinders ( x ≈ 5–8). Chemical microstructure of the I arm [poly( cis 1, 4‐isoprene)] versus poly(3, 4‐isoprene) is shown to play important role in affecting morphological behavior. To reconcile differences between ISV‐ x star morphologies reported in the literature and those reported herein, even for the same composition, effects of the microstructure of I arm on the Flory–Huggins parameter between I and V arms were taken into account in a qualitative manner. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 1491–1504 Abstract : A deeply integrated study of poly(styrene‐b‐ cis ‐1, 4‐isoprene‐b‐2‐vinylpyridine) miktoarm star terpolymers interweaving transmission electron microscopy, small‐angle X‐ray scattering, self‐consistent field theory, and rheology, paints a coherent picture of this model system on the intricate self‐assembly forming many nonconventional morphologies like, for example, Archimedean tilings. Variation of the P2VP chain length (x) provides access to a plethora of experimental morphologies consistent with simulations. The simulations also reconcile differences encountered between morphologies formed by stars containing cis ‐1, 4‐PI studied here, and 3, 4‐PI reported previously.